Pendampingan Masyarakat dalam Design Program Incentive Travel sebagai Produk Wisata di Desa Wisata Pulau Harapan Kepulauan Seribu Daerah Khusus Jakarta - Yosi Erfinda; Rahmat Darmawan; Revi Agustin Aisyianita; Rinie Octaviany Hasan; Siti Nurliani Putri; Fatinah Rafa Andini (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Harapan Island Tourism Village is administratively located in the North Thousand Islands, Harapan Island Village, Jakarta City. The tourism potential of Pulau Harapan is conservation, preservation, and marine tourism. This tourist village is a favorite destination for tourists (leisure) and corporate market tourists. This is proven by the local guide’s experience in accompanying tourist visits. This is the focus of community service to develop the potential of b leisure tourism through Incentive Travel. The goal is to explore the potential of bleisure tourism to increase Incentive Travel tourist visits, which are in line with the city of Jakarta as a bleisure tourism center. This activity was held offline from March 16‒April 30, 2024 on Harapan Island using the Participatory Action Research (PAR) method. Starting with five PAR cycles, including know, understand, plan, act, change, where each stage relied on community involvement in solving problem priorities. This was followed by a Forum Group Discussion (FGD) activity, where before (pre-test) and after the activity (post-test), participants measured their knowledge and abilities regarding the tourism potential of Incentive Travel, showing the achievement of good success of the activity. This is an effort to increase public participation in exploring Incentive Travel tourism as a tourism product on Harapan Island.